"슬레이터 1"의 두 판 사이의 차이
둘러보기로 가기
검색하러 가기
26번째 줄: | 26번째 줄: | ||
* Use the following <br><math>\sum_{r=0}^{n}\frac{(1-aq^{2r})(-1)^{r}q^{\frac{1}{2}(r^2+r)}(a)_{r}(c)_{r}(d)_{r}a^{r}}{(a)_{n+r+1}(q)_{n-r}(q)_{r}(aq/c)_{r}(aq/d)_{r}c^{r}d^{r}}=\frac{(aq/cd)_{n}}{(q)_{n}(aq/c)_{n}(aq/d)_{n}}</math><br> | * Use the following <br><math>\sum_{r=0}^{n}\frac{(1-aq^{2r})(-1)^{r}q^{\frac{1}{2}(r^2+r)}(a)_{r}(c)_{r}(d)_{r}a^{r}}{(a)_{n+r+1}(q)_{n-r}(q)_{r}(aq/c)_{r}(aq/d)_{r}c^{r}d^{r}}=\frac{(aq/cd)_{n}}{(q)_{n}(aq/c)_{n}(aq/d)_{n}}</math><br> | ||
* Specialize<br><math>a=1,c=0,d=\infty</math><br> | * Specialize<br><math>a=1,c=0,d=\infty</math><br> | ||
− | * Bailey pair<br><math>\alpha_{0}=1</math>, <math>\alpha_{ | + | * <br> Bailey pair<br><math>\alpha_{0}=1</math>, <math>\alpha_{r}=(-1)^{n}(1+q^r)q^{\frac{1}{2}r(r-1)}</math><br><math>\beta_n=\sum_{r=0}^{n}\frac{\alpha_r}{(x)_{n-r}(q)_{n+r}}=\sum_{r=0}^{n}\frac{\alpha_r}{(q)_{n-r}(q)_{n+r}}=\frac{1}{(q)_{n}(-q)_{n}}</math><br> |
2011년 11월 12일 (토) 12:17 판
이 항목의 수학노트 원문주소
노트
항등식의 종류
베일리 쌍의 유도
- Use the following
\(\sum_{r=0}^{n}\frac{(1-aq^{2r})(-1)^{r}q^{\frac{1}{2}(r^2+r)}(a)_{r}(c)_{r}(d)_{r}a^{r}}{(a)_{n+r+1}(q)_{n-r}(q)_{r}(aq/c)_{r}(aq/d)_{r}c^{r}d^{r}}=\frac{(aq/cd)_{n}}{(q)_{n}(aq/c)_{n}(aq/d)_{n}}\) - Specialize
\(a=1,c=0,d=\infty\) -
Bailey pair
\(\alpha_{0}=1\), \(\alpha_{r}=(-1)^{n}(1+q^r)q^{\frac{1}{2}r(r-1)}\)
\(\beta_n=\sum_{r=0}^{n}\frac{\alpha_r}{(x)_{n-r}(q)_{n+r}}=\sum_{r=0}^{n}\frac{\alpha_r}{(q)_{n-r}(q)_{n+r}}=\frac{1}{(q)_{n}(-q)_{n}}\)